Size‐structured vulnerability of the colonial cyanobacterium, Microcystis aeruginosa, to grazing by zebra mussels (Dreissena polymorpha). (5th December 2013) - White, Jeffrey D.; Sarnelle, Orlando
Summary We quantified the vulnerability of colonies of the bloom‐forming cyanobacterium, Microcystis aeruginosa, to grazing by the invasive filter‐feeding zebra mussel (Dreissena polymorpha) as a function of size in both organisms with laboratory feeding experiments. In one experiment, size‐selectivity of 16‐ to 21‐mm mussels was assessed for a single M. aeruginosa clone across a wide size range (~5–88 μm median equivalent diameter, ED). Consumption of colonies ≥80 μm median ED (109 μm median maximum linear dimension) was undetectable, indicating a size threshold of grazing invulnerability. Smaller colonies and single cells were consumed at rates similar to a highly palatable alga (Ankistrodesmus). In a second experiment, the size‐selectivity of three size classes of mussels (8–11, 17–20 and 25–28 mm shell length) was assessed across three size classes of M. aeruginosa (~32–75 μm median ED). There were no systematic differences in the abilities of the different mussel size classes to consume the largest colonies within this size range. An 8‐year field survey of the M. aeruginosa population in Gull Lake, MI (U.S.A.), the source of the experimental organisms, revealed that median colony size consistently decreased during each summer, from above to below the size threshold of effective mussel feeding we identified, which suggests major within‐season shifts in the overall vulnerability of the M. aeruginosa population to mussel grazing. Variation in the size structure of M. aeruginosa may help explain highly variable effects of D. polymorpha on the dynamics of this harmful phytoplankter within and across systems.